2018
DOI: 10.1016/j.jtcvs.2018.03.034
|View full text |Cite
|
Sign up to set email alerts
|

A heart valve is no stronger than its weakest link: The need to improve durability of pericardial leaflets

Abstract: Central Message Innovative anticalcification treatments can improve the durability of surgical and transcatheter valve bioprostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Partial phospholipid membrane extraction with alcohols, for instance, has found its way into some commercial tissue valves. LivaNova uses octanediol-ethanol for its FREE treatment, St. Jude/Abbot uses ethanol for its Linx-treatment of its Trifecta valve and so does Edwards Life-Sciences in its Thermafix heat treatment used for its Perimount valves (84). Single centre, long-term studies with these valves have shown remarkably encouraging results in young patients (85).…”
Section: Patients In Need Of Cardiac Surgery and Patient's Needsmentioning
confidence: 99%
“…Partial phospholipid membrane extraction with alcohols, for instance, has found its way into some commercial tissue valves. LivaNova uses octanediol-ethanol for its FREE treatment, St. Jude/Abbot uses ethanol for its Linx-treatment of its Trifecta valve and so does Edwards Life-Sciences in its Thermafix heat treatment used for its Perimount valves (84). Single centre, long-term studies with these valves have shown remarkably encouraging results in young patients (85).…”
Section: Patients In Need Of Cardiac Surgery and Patient's Needsmentioning
confidence: 99%
“…Therefore, the additional fixation and stabilization of the collagen scaffold with GA might be required [ 17 ]. However, the free aldehyde groups of GA are associated with cellular toxicity [ 18 ], while conjugated GA may contribute to graft calcification [ 19 , 20 ]. Washing and detoxifying with solutions that can bind the free aldehyde groups prior to implantation can improve durability and biocompatibility [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these processes, fixing tissues with glutaraldehyde and rendering them inert to the recipient's body is most widely adopted, despite significant drawbacks of such a method as described earlier. 2 Decellularization of xenografts and their use as replacement scaffolds has been an area of much interest, as such tissue maintains a highly complex, 3-dimensional extracellular matrix structure with a mix of different proteins that are often challenging to replicate using human-made methods such as 3-dimensional printing and electrospinning. Devoid of donor cells, these bare extracellular matrix materials could not only provide scaffolding at the implant site but potentially recellularize with the recipient's cells for in situ tissue reconstitution.…”
mentioning
confidence: 99%